2020
DOI: 10.1038/s41467-020-19435-z
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation by the polyhomeotic sterile alpha motif compartmentalizes Polycomb Group proteins and enhances their activity

Abstract: Polycomb Group (PcG) proteins organize chromatin at multiple scales to regulate gene expression. A conserved Sterile Alpha Motif (SAM) in the Polycomb Repressive Complex 1 (PRC1) subunit Polyhomeotic (Ph) has been shown to play an important role in chromatin compaction and large-scale chromatin organization. Ph SAM forms helical head to tail polymers, and SAM-SAM interactions between chromatin-bound Ph/PRC1 are believed to compact chromatin and mediate long-range interactions. To understand the underlying mech… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
116
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(124 citation statements)
references
References 97 publications
8
116
0
Order By: Relevance
“…Considering the existence of cPRC1 and recent identification of BAHCC1 BAH as H3K27me3-specific readers (17), the chromodomain (cPRC1)- and BAH-mediated functional readout of H3K27me3 can coexist in mammalian cells, imparting their respective gene-silencing effects through distinctive molecular pathways. Besides a catalytic function for inducing H2AK119ub1, cPRC1 induces chromatin compaction via cofactor-mediated phase separation and condensation formation (1214). On the other hand, BAHCC1 (17) and BAHD1 both interact with HDACs, thus linking H3K27me3 together with histone deacetylation, an integral step of gene repression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the existence of cPRC1 and recent identification of BAHCC1 BAH as H3K27me3-specific readers (17), the chromodomain (cPRC1)- and BAH-mediated functional readout of H3K27me3 can coexist in mammalian cells, imparting their respective gene-silencing effects through distinctive molecular pathways. Besides a catalytic function for inducing H2AK119ub1, cPRC1 induces chromatin compaction via cofactor-mediated phase separation and condensation formation (1214). On the other hand, BAHCC1 (17) and BAHD1 both interact with HDACs, thus linking H3K27me3 together with histone deacetylation, an integral step of gene repression.…”
Section: Discussionmentioning
confidence: 99%
“…As a support, mutation of the histone H3K27 site or its modifying enzymes occur recurrently in a range of human diseases, such as cancer and developmental syndrome (69). A prevalent model for functional transduction of H3K27me3 in mammals is that H3K27me3 is read and bound by chromodomain harbored within the chromobox (CBX) component of canonical Polycomb repressive complex 1 (cPRC1), which can induce gene silencing at least partly through mono-ubiquitination of histone H2A lysine 119 (H2AK119ub1) (2,3,10,11) and/or a phase separation-mediated chromatin compaction mechanism (1214). However, emerging evidence has shown that, in mammalian cells, H3K27me3 is also ‘sensed’ and bound by a second class of “reader” modules termed Bromo-Adjacent Homology (BAH), which exist within chromatin regulators such as BAH D omain Containing 1 (BAHD1) (15,16) and BAH and C oiled- c oil Domain-containing Protein 1 (BAHCC1) (17).…”
Section: Introductionmentioning
confidence: 99%
“…PcG proteins can directly silence transcription by, for example, preventing the binding of chromatin remodeling complexes [ 117 ]. In addition, polycomb proteins can indirectly block transcription through a combination of local chromatin compaction [ 118 , 119 , 120 , 121 ], loop formation [ 106 , 107 ], as well as phase separation [ 24 , 28 , 122 ].…”
Section: Facultative Heterochromatinmentioning
confidence: 99%
“…In this work, we assumed that such contacts were dependent only on the genomic distance and were not affected by the local epigenetic landscape. However, PRC1 that binds to H3K27me3 may form condensate (45,(76)(77)(78) , the so-called Polycomb bodies, and may subsequently impact the local 3D organization of the locus (79,80), an increase compaction may in turn facilitate spreading (81)(82)(83). Accounting for this positive feedback loop between longrange spreading and 3D chromosome organization may allow a better characterization of the role of genome folding in epigenetic regulation (84,85).…”
Section: Discussionmentioning
confidence: 99%